(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
The digital transformation of credit unions has become an urgent matter as it becomes an important pillar to fulfill ongoing member needs and maintain organizational competitiveness. However, digital transformation influences credit union activities and may have some potential consequences for their performance and, most importantly, the well-being of credit union members, both in a positive and negative direction. The effectiveness of the digital transformation of credit unions depends on how members of the credit union respond to the digitized elements and how credit unions provide an environment to recognize, learn, and grow with digitalization. This paper, utilizing Amartya Sen’s capability approach, aims to offer an alternative operational framework that translates digitalization into members’ well-being within the credit union operation context. This research contributes to the development of an effective and sustainable model of digital transformation for credit unions.